Physicochemical properties and cytotoxicity of brown carbon produced under different combustion conditions. (1st January 2021) - Atwi, Khairallah; Mondal, Arnab; Pant, Jitendra; Cheng, Zezhen; El Hajj, Omar; Ijeli, Ifeoma; Handa, Hitesh; Saleh, Rawad
Abstract: Light-absorbing organic particulate matter (PM), or brown carbon (BrC), may constitute an important fraction of combustion PM. Here, we investigate the effect of combustion conditions on the molecular sizes of BrC, their light-absorption properties, and their cytotoxicity. We used toluene in a combustion reactor with highly controlled conditions to produce two different types of BrC under two conditions corresponding to smoldering and near-flaming combustion, with temperatures of 670 °C and 1035 °C, respectively. We performed online measurements of the size distributions and light-absorption properties of the BrC. The BrC produced at 1035 °C was more light absorbing, with an imaginary component of the refractive index at 532 nm ( k 532 ) an order of magnitude larger than that of the BrC produced at 670 °C. We also collected samples for offline chemical characterization using laser desorption ionization (LDI) mass spectrometry. The LDI mass spectra showed that the BrC produced at 1035 °C was composed of species with significantly larger molecular sizes than the BrC produced at 670 °C. Using human lung epithelial cells, we conducted in vitro cytotoxicity analysis on the two types of BrC with doses ranging from 3.5 to 136.0 μg of BrC/ml. After 24-h exposure, the viability of the cells was assessed using a WST-8 assay. The cytotoxicity analysis showed that, for both BrC samples, the cells exhibited a clear dose-dependent response with significant BrC cytotoxicity that plateaued at the higher doses. However, while the viability of cells exposed to the BrC produced at 1035 °C reached a minimum of around 65% at the highest dose, the BrC produced at 670 °C proved to be significantly more toxic, with the viability dropping asymptotically to 25%. The results presented here suggest that organic PM of smaller molecular sizes produced under lower temperature, smoldering combustion could be significantly more toxic than that of larger molecular sizes produced under higher temperature, flaming conditions. The use of a single-molecule fuel in a highly controlled combustion setup distinguishes this work from experiments that rely on real-life sources and combustion setups, where different combustion conditions could be occurring simultaneously and clouding the conclusions. Highlights: Brown carbon particles produced from highly controlled combustion setup. Starkly different molecular composition of particles under low and high temperatures. Lower temperature particles comprise smaller molecules. Smaller molecules significantly more cytotoxic to lung epithelial cells in vitro .